Bond behaviour of high‐strength concrete flexural member under low cyclic fatigue loading. Issue 7 (27th March 2013) - Abbass, W.; Siddiqi, Z. A.; Aslam, F.; Hussain, R. R.; Ahmed, S.
ABSTRACT Use of high‐strength concrete can lead to more economical design reducing the material requirements, weight of structure and extended service life of structure. The effect of fatigue loading is more prominent on the structures using high‐strength concrete. Bond between concrete and reinforcing bars is a major factor affecting the performance and sustainability of reinforced concrete structures. Less research is available on the effect of low cyclic fatigue loading on the bond strength of high‐strength concrete. In this research, reinforced concrete beams (1165 × 150 × 225 mm) were tested under low cyclic loading with different stress range levels. It can be concluded that the bond strength of high‐strength concrete is more than for normal‐strength concrete. Low‐cyclic fatigue loading decreased the bond strength under monotonic loading by about 43–45%. Energy dissipation during cycling is found to be good. At higher cycles, energy dissipation decreased because of local damages in front of bar ribs. With the increase in number of cycles, change in slip behaviour was found.